Evidence for Attentional Phenotypes in Infancy and Their Role in Visual Cognitive Performance - Shannon Ross-Sheehy (Brain Sciences, 2020)
Infant visual attention rapidly develops during the first year of life, playing a pivotal role in the way infants process, learn, and respond to their visual world. It is possible that individual differences in eye movement patterns shape early experience and thus subsequent cognitive development. If this is the case, then it may be possible to identify sub-optimal attentional behaviors in infancy, before the emergence of cognitive deficit. In Experiment 1, a latent profile analysis was conducted on scores derived from the Infant Orienting with Attention (IOWA) task, a cued-attention task that measures individual differences in spatial attention and orienting proficiency. This analysis identified three profiles that varied substantially in terms of attentional efficiency. The largest of these profiles (“high flexible”, 55%) demonstrated functionally optimal patterns of attentional functioning with relatively rapid, selective, and adaptive orienting responses. The next largest group (“low reactive”, 39.6%) demonstrated low attentional sensitivity with slow, insensitive orienting responses. The smallest group (“high reactive”, 5.4%) demonstrated attentional over-sensitivity, with rapid, unselective and inaccurate orienting responses. A linear mixed effect model and growth curve analysis conducted on 5- to 11-month-old eye tracking data revealed significant stable differences in growth trajectory for each phenotype group. Results from Experiment 2 demonstrated the ability of attentional phenotypes to explain individual differences in general cognitive functioning, revealing significant between-phenotype group differences in performance on a visual short-term memory task. Taken together, results presented here demonstrate that attentional phenotypes are present early in life and predict unique patterns of growth from 5 to 11 months, and may be useful in understanding the origin of individual differences in general visuo-cognitive functioning.